Exosomal miR-590-5p in Serum as a Biomarker for the Diagnosis and Prognosis of Gastric Cancer - Zheng, Guo-Dian; Xu, Zhi-Yuan; Hu, Can; Lv, Hang; Xie, Hua-Xia; Huang, Ting; Zhang, Yan-Qiang; Chen, Gui-Ping; Fu, Yu-Fei; Cheng, Xiang-Dong (Frontiers in Molecular Biosciences, 2021)
Background: Gastric cancer (GC) is a common malignancy with low 5-year overall survival. The aims of this study are to investigate the expression of exosomal miRNA-590-5p (miR-590-5p) in gastric cancer(GC) and to assess the correlation between exosomal miR-590-5p and respective clinical pathological characteristic. Methods: Exosomal miRNAs was identified after comparing 3 pairs of pre- and post-operative serum from 3 gastric cancer patients by next generation sequencing technology. Serum samples from 168 gastric cancer patients and 50 matched controls were collected and exosomal RNAs were extracted. After which, miR-590-5p expression was analysed by quantitative reverse transcription polymerase chain reaction (qRT-PCR) and further correlated with patients’ clinicopathological parameters as well as follow-up data. MGC-803 cells and HGC-27 cells were treated with miR-590-5p mimics followed by monitoring changes in cell migration and invasion. Results: It was revealed that the expression levels of exosomal miR-590-5p in the healthy control group, early (I and II) stage group and late stage (III) group were 30.34±6.35，6.19±0.81 and 2.9±0.19，respectively(all P<0.05). ROC (receiver-operating characteristic curve) showed that the AUC (area under curve) of exosomal miR-590-5p was 0.810 with 63.7 % sensitivity and 86 % specificity. Serum exosomal miR-590-5p expression was related with clinical stage (P = 0.008) and invasion depth (P<0.001). Moreover, Kaplan-Meier analysis showed a correlation between decreased exosomal miR-590-5p level and reduced overall survival (P <0.001). The multivariate Cox regression analyses showed that the miR-590-5p could act as an independent prognostic indicator. Furthermore, up-regulation of miR-590-5p inhibited cell migration and invasion in MGC-803 cells and HGC-27 cells. Conclusions: The serum exosomal miR-590-5p expression level could be a potential and helpful noninvasive biomarker for the early detection and prognosis of GC, Furthermore, miR-590-5p may function as a cancer suppressor by positively regulating the malignant potentials of gastric cancer.